KEDUDUKAN TANAH ULAYAT DALAM PERSPEKTIF KONSTITUSI INDONESIA” (Undang-Undang Dasar Negara Republik Indonesia Tahun 1945) - Hairan Hairan (Yuriska: Jurnal Ilmiah Hukum, 2017)
The traditional communal land is part of the rights of indigenous peoples are also the same is true with other rights. Only in the 1945 constitution has been no firmness to the Status of Communal Land as a value for the communal land, as well as a reflection of the existence of the Republic of Indonesia. In the plurality and diversity of society and their rights is a universal value and is considered a significant religious value, namely land. The existence of great importance that the State is dominating power in determining the allocation of land without making the communal land as one of the presence and diversity of law and its object in Indonesia. So that the rights of control by the State without clear boundaries.